2010
DOI: 10.1007/s12576-009-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

Exertional dyspnea-related acidotic and sympathetic responses in patients with sequelae of pulmonary tuberculosis

Abstract: The objective of this study was to investigate whether exertional dyspnea correlates with exercise responses, especially arterial blood pH and plasma norepinephrine (NE) changes, in patients with sequelae of tuberculosis (TBsq). Cardiopulmonary exercise testings were performed in 49 TBsq patients and 9 controls. Each group had a break point in the dyspnea, plasma lactate, and plasma NE changes during exercise, all of which occurred at a similar exercise point. In TBsq patients in both exercise phases before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The plasma norepinephrine levels seemed to be inhibited at the iso-time point (Table 3). Given the reported negative connotations of sympathetic activation in cardiac as well as respiratory disease patients [22-26], sympathetic inhibition may have positive consequences in COPD. These findings suggest that underweight patients with COPD who undergo exercise training can only increase their endurance time, efficiently decreasing Vo2 and plasma norepinephrine levels.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma norepinephrine levels seemed to be inhibited at the iso-time point (Table 3). Given the reported negative connotations of sympathetic activation in cardiac as well as respiratory disease patients [22-26], sympathetic inhibition may have positive consequences in COPD. These findings suggest that underweight patients with COPD who undergo exercise training can only increase their endurance time, efficiently decreasing Vo2 and plasma norepinephrine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infection such as pulmonary tuberculosis is not generally considered to be a common cause of TTC. However, a few reports suggest that there is a higher plasma norepinephrine concentration in pulmonary tuberculosis patients compared to normal people, which is a typical accepted pathophysiological mechanism of TTC4,5. Thus, we postulate that pulmonary tuberculosis may be a possible precipitant of TTC.…”
Section: Discussionmentioning
confidence: 73%
“…An intimate relationship between the increase in plasma norepinephrine and dyspnea intensity during exercise has also been observed in patients with other respiratory diseases, including idiopathic pulmonary fibrosis 20 and sequelae of pulmonary tuberculosis. 21 Also, Clark et al 33 found that the administration of yohimbine increased norepinephrine release in healthy individuals, and this increase was associated with increased ventilatory response and an increased sensation of exertion during steady-state exercise. Thus, the increase in norepinephrine induced by exercise could also contribute to the increase in both ventilation and the sensation of breathlessness.…”
Section: Relationship Between Dyspnea and Arterial Norepinephrinementioning
confidence: 99%